Influência da idade na atividade do sistema eferente nas propriedades mecânicas da cóclea de ouvintes normais - De Oliveira, Jerusa Roberta Massola; Fernandes, João Candido [UNESP]; Costa Filho, Orozimbo Alves (Elsevier, 2009)
The medial olivocochlear tract has efferent control over the outer hair cells, regulating the slow contractions and damping the fast ones. Using ipsilateral, contralateral or bilateral otoacoustic emissions amplitude studies, it is possible to estimate the conditions of this tract, since the effect resulting from the reduction/suppression of these emissions indicate the tract's functioning. Aging implies an activity reduction in the central auditory system, because of the degeneration of the structures involved in hearing skills. Aim: our goal was to investigate the effects of age on the activities of this tract on the cochlea, through the analysis of the emissions' amplitude with contralateral acoustic stimulation. Materials and methods: Our series was made up of 75 individuals grouped according to age. The methodology was conventional, with a linear click and a white noise. Case study: the analysis considered the response from both ears and the comparison between the groups. Results: the results show a statistically significant difference between the emissions' response with and without contralateral acoustic stimulation in the individuals between 20 and 39 years of age. The emissions reduction/suppression effect reduced with age (fourth decade). Conclusion: aging impairs the tract effectiveness. © Revista Brasileira de Otorrinolaringologia.
Age impact on the eferent system actitivies in cochlear mechanical properties in normal hearing individuals
Keywords: Aging; Hearing; Organ of corti